DEIKSIS PERSONA BAHASA INDONESIA DIALEK AMBON - Taufik (Universitas Hasanuddin, 2017)
This study aimed to explain the use of the lexeme of personal deixis of the Indonesian language in ambonese dialect. This research was a qualitative descriptive research which try to study linguistic phenomena by sociopragmatic approach. The data have been obtained, classified and analyzed descriptively with qualitative approach. The results show that, the use of deixis forms of lexemic personality of the Indonesian language in Ambonese dialect comprised into the first single personal pronoun, the second single personal pronoun, and the sole third personal pronoun. The use of the kinite lexeme of the Indonesian dialect of Ambon has different characteristics from other languages. Such distinctiveness is a form of deixis persona that can have various references and meanings. It is strongly influenced by the social context inherent in Ambonese society.